Jihad fi Sabilillah: Insights From a Thematic Hadith Study on Spiritual, Social, and Educational Dimensions - Siar Ni'mah; Firdaus, Firdaus; Amir, Amir Hamzah; Umar (MADINAH, 2025)
Jihad has become a continuously evolving narrative, both in terms of perspective and implementation. This research on jihad aims to comprehensively understand how jihad is wisely interpreted from a hadith perspective. Since this study focuses on hadiths concerning jihad, it is a library research with a thematic hadith (hadis maudhu'i) scholarly approach. The books *Kunuz as-Sunnah* and *Maktabah Syamilah* were used as two media to trace hadiths about jihad, which were then analyzed using the thematic analysis method. The results of this study confirm: 1) Hadith texts on jihad are found in both the six and nine major hadith collections; 2) The hadiths on jihad found provide at least eleven thematic mappings, such as the call to jihad, jihad as the most excellent deed, deeds on Ayyam al-Tasyriq being more excellent than jihad, jihad as the deed closest to paradise, jihad as the most beloved deed, deeds with rewards similar to jihad, jihad as the pinnacle of deeds, forms of jihad, the abolition of one form of jihad, the reward of jihad, and indicators for obtaining the reward of jihad; 3) Contextually, jihad is no longer understood solely as war, as implemented during the time of Prophet Muhammad ﷺ which was indeed appropriate for the situation, but today it can be more flexible in accordance with the spirit of jihad, such as social and educational jihad.